2015
DOI: 10.5539/gjhs.v8n5p154
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Health Promoting Programs on Patient's Life Style After Coronary Artery Bypass Graft–Hospitalized in Shiraz Hospitals

Abstract: Background:Health promotion is an essential strategy for reduction of health disparities. Health promotion includes all activities that encourage optimum physical, spiritual, and mental functions. The aim of this study was to determine the impact of a Health Promotion Program (HPP) on behavior in terms of the dimensions of the Health Promoting Lifestyle Profile (HPLP) in patients after Coronary Artery Bypass Graft (CABG).Methods and Materials:In this clinical trial study, 80 patients who had undergone CABG sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
4
16
0
2
Order By: Relevance
“…This study resorted to various strategies during an eight-week outpatient program with a weekly hour-and-a half-session each. [22] In the study by Safabakhsh et al (2016) involving eighty participants who had undergone coronary surgery and were submitted to a health promotion program, there were positive results in the diet variable at three-month follow up. The progress of the EG and the difference between the groups after intervention are significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study resorted to various strategies during an eight-week outpatient program with a weekly hour-and-a half-session each. [22] In the study by Safabakhsh et al (2016) involving eighty participants who had undergone coronary surgery and were submitted to a health promotion program, there were positive results in the diet variable at three-month follow up. The progress of the EG and the difference between the groups after intervention are significant.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the CG did not reveal an improvement in the diet variable (p < .265). [23] In addition, Sundin et al (2003) report positive results in the eating habits of 132 individuals submitted to behavioural rehabilitation programs when compared to those who only receive standard care, in their study conducted on patients suffering from coronary diseases (AMI, CABG, PTCA) with a twelve-month follow up. [24] The result of this study seem to align with the result of the referenced literature, even having the CG sometimes showing evidence of improvement and at other times showing none.…”
Section: Discussionmentioning
confidence: 99%
“…Mahdipour et al studied the effect of educational intervention on a health-promoting lifestyle and reported that although nutrition was one dimension of lifestyle, its score did not change significantly after educational intervention. 28 Safabakhsh et al 29 examined the effect of health-promoting programs on patient lifestyle after coronary artery bypass surgery and found that the HPLP nutrition subscale score increased significantly after intervention in the experimental group (19.7±0.135 versus 31.3±0.258). The HPLP nutrition subscale score of these patients before intervention was lower than that of the present study, although the score was higher after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Literatürde, sağlığı geliştirme modeli kullanılarak yapılan eğitimlerin bireylerin stres yönetimde faydalı olduğu bildirilmiştir. 17,27,34 Safabakhsh'ın (2016) 27 çalışmasında eğitim öncesi ve sonrası değerlendirilen deney ve kontrol gruplarında; deney gruplarının stres yönetimi puan ortalamalarında anlamlı derecede artış bulunmuştur. Buna göre, bireylere sağlığı geliştirme modeli doğrultusunda verilen eğitimin davranış değiştirmede etkili olduğu ve eğitim alan bireylerin stres yönetiminde daha başarılı oldukları belirtilmiştir.…”
Section: Stres Yönetimiunclassified
“…17,27 Diyet-Mesane İrritanlarından Kaçınılması-Konstipasyonun Önlenmesi Özel bir diyet olmamasına rağmen, bazı besinlerin mesane irritabilitesini ve diürezi artırdığı, bu nedenle aşırı aktif mesane, sıkışma tipi idrar kaçırma gibi PTD semptomlarını şiddetlendirdiği kanıtlanmıştır. 27 'nın koroner arter bypass greft ameliyatı olan hastalar ile yaptıkları deney kontrol çalışmasında; sağlığı geliştirme modeli doğrultusunda hazırlanan eğitim programı deney grubuna 3 ay içerisinde 2 kez (6. ve 10. haftalarda) uygulanmıştır. Çalışma sonucunda deney grubunun kontrol grubuna göre istenilen diyet programına uyduğu istatiksel olarak anlamlı bulunmuştur.…”
unclassified